THE TRESPASSER IN LITERARY CINEMA: COLLECTIVE TRANSLATION AND DIALOGISM IN THE POST-RETOMADA - Silva Junior, Augusto Rodrigues da; Gandara, Lemuel da Cruz (Cadernos de Educação Tecnologia e Sociedade, 2016)
From the novel O invasor (2002), written by Marcal Aquino, and its adaptation for cinema The Trespasser, directed by Beto Brant, also released in 2002, we do an analytical reflection of filmic elements such as photography and screenplay focused on the collective translation and aesthetics of urban violence ideas in the Post-Retomada of Brazilian literary cinema. The theoretical and critical perspective are based on the dialogism funded by Mikhail Bakhtin and in the theoretical studies of Silva Jr. and Gandara, Xavier and Nagib.